The Effect of Ferntation Duration of Aren (Arenga pinnata Merr) Stem Waste on Chemical Composition and In Vitro Digestibility - Hanim, Chusnul; Yusiati, Lies Mira; Nugraheni, Ajeng Pratiwi (2015)
This research was conducted to determined the effect of fermentation duration of aren stem waste on chemical composition and in vitro digestibility. In the beginning of fermentation, 0.3 g biostaterand 1.2 g urea was added to 300 g aren stem waste. Fermentation was conducted anaerobically at room temperature for 10, 20, 30 40 d with three replicate for each treatment. The samples of fermented aren stem waste were analyzed physical quality 9texture, odor, color, growth of fungi and PH), chemical composition, and in vitro digestibility. The data obtained were analyzed variance following one way design, and continued by Dunchan’s new multiple range test for any differance between treatments. Result showed that fermentation gave soft texture, more acidic odor, and dark brown color than fresh aren stem waste. The fermentatin decreased pH of aren steam waste up to less than 4,2 (P,0.01) at 20, 30 and 40 d (4.2. 3.82 and 4.17). The chemically composition of fermented aren stem waste increased after a longer fermentation time with the lowest value 31.57%(P,0.01) at 40 d of fermentation time. After 30 d fermentation, dry matter, organic matter, and crude fiber digestibility increased 12,84%, 17.18%, and 20.91% respectively compared to 10 d of fermentation time (P<0.01). It could be concluded that 30 d was the most effective of fermentation duration of aren stem waste which increased chemical composition and in vitro digestibility